Global Marketing Systems in the Dairy Sector: A Comparison of Selected Countries - Manjunatha, A. V.; Gana Shruthy, M. K.; Ramachandra, V. A. (Indian Journal of Marketing, 2013)
This paper focuses on the global dairy sector in general, and milk marketing systems in particular. The dairy sector is multifunctional in nature, and contributes to sustainable agricultural development and food security. The global trade is dominated by developed countries, contributing to 62% of the imports and 92% of the exports. Global production and consumption are increasingly imposing pressure to produce and process more, keeping in the mind the aspects of quality and efficiency. The development of dairy markets is affected by access to milk markets and market distortions. Additionally, the development of dairy markets depends on the governments' involvement in regulating production and marketing of milk and milk products. In this regard, comparison of marketing systems across countries considering supply, demand, prices, and trade is important for a clear understanding of the complexities, performance, and challenges in the systems. The analysis indicates that although the production has increased over years in regulated (USA), deregulated (Australia), and informal (India) dominated milk markets, but consumption has increased only in the informal dominated markets. The processing is greater than 90% in Australia and USA, while this is only 18% in India, indicating backwardness of the Indian dairy sector. The farmers' share in consumers' basket is increasing in Australia, decreasing in USA, and is stable in India, representing a higher benefit to producers in deregulated markets and stability of the market in the informal sector dominated market. The milk prices are closer to the world market price in regulated markets as compared to the deregulated and informal markets, signifying higher regulation of production and marketing in USA. The self-sufficiency and performance of the Australian dairy sector is comparatively better because the dairy farms are competing in the international markets. The successful policy interventions in informal markets of Kenya and India indicates that these markets have the potential to improve income and employment, but impose constraints on quality and trade. These issues can be tackled by following an integrated approach in gradual conversion of informal to the formal sector through proper education and training, which has the potential for the overall development of the dairy industry.